Interleukin-1 mRNA-expressing macrophages in human chronically inflamed gingival tissues. - Matsuki, Y. (1991)
Interleukin-1 (IL-1)-producing cells in inflamed gingival tissues obtained from patients with periodontitis were examined by combined immunohistochemistry and in situ hybridization. Macrophages, T cells, B cells, and endothelial cells were visualized in the lesions by the immunoperoxidase method using specific antibodies to each cell type. Subsequent in situ hybridization using 35S-labeled synthetic oligonucleotide probes complementary to human IL-1 alpha and IL-1 beta mRNA showed IL-1 transcripts in macrophages predominantly but not in T cells or B cells. Neither fibroblasts nor keratinocytes contained the IL-1 message to any significant extent. Endothelial cells also were essentially negative for IL-1 messages. These findings indicate that IL-1 is produced principally by macrophages in inflamed gingival tissues of humans.